The dissociation between command following and communication in disorders of consciousness: an fMRI study in healthy subjects - Osborne, Natalie R.; Owen, Adrian M.; Fernández-Espejo, Davinia (Frontiers in Human Neuroscience, 2015)
Neuroimaging studies have identified a subgroup of patients with a Disorder of Consciousness (DOC) who, while being behaviourally non-responsive, are nevertheless able to follow commands by modulating their brain activity in motor imagery tasks. These techniques have even allowed for binary communication in a small number of DOC patients. However, the majority of patients who can follow commands are unable to use their responses to communicate. A similar dissociation between present command following and absent communication abilities has been reported in overt behavioural assessments. However, the neural correlates of this dissociation in both overt and covert modalities are unknown. Here, we used functional magnetic resonance imaging to explore the neural mechanisms underlying command following and selection of responses for binary communication using either executed or imagined movements. 15 healthy participants executed or imagined two different types of arm movements that were either pre-determined by the experimenters (command following) or decided by them (action selection). Action selection involved greater activity in high-level associative areas in frontal and parietal regions than command following. Additionally, motor execution, as compared to motor imagery, activated contralateral motor cortex, while the opposite contrast revealed activation in the ipsilateral sensorimotor cortex and the left inferior frontal gyrus. Importantly, there was no interaction between the task (command following / action selection) and modality (motor imagery / motor execution). Our results suggest that the neural processes involved in following a motor command or selecting between two motor actions are not dependent on how the response is expressed (via motor execution/imagery). They also suggest a potential neural basis for the distinction in cognitive abilities seen in DOC patients.